2001
DOI: 10.3109/13506120108993819
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cholyl-leu-val-phe-phe-ala-OH as an inhibitor of amyloid beta-peptide polymerization

Abstract: Cholyl-LVFFA-OH (1, PPI-368) is an organic-modified peptide based on the sequence of amyloid beta-peptide (A beta). It is a potent and selective inhibitor of A beta polymerization that blocks the formation of neurotoxic species of A beta. In a nucleation-dependent polymerization assay of 50 microM A beta(1-40), equimolar concentrations of PPI-368 block polymerization based on turbidity and electron microscopy. Monomeric A beta(1-40) and A beta(1-42) are non-toxic when incubated with neuronal cell lines, but be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Following these promising results, this group's strategy was to add to the recognition element a bulky group in order to interfere with Aβ polymerization [82,83]. They generated several derivatives of Aβ with Nterminal modifications.…”
Section: Inhibiting Aβ Aggregation By Small Rationallydesigned Peptidesmentioning
confidence: 97%
See 1 more Smart Citation
“…Following these promising results, this group's strategy was to add to the recognition element a bulky group in order to interfere with Aβ polymerization [82,83]. They generated several derivatives of Aβ with Nterminal modifications.…”
Section: Inhibiting Aβ Aggregation By Small Rationallydesigned Peptidesmentioning
confidence: 97%
“…Equimolar concentrations of cholyl-LVFFA-OH potently inhibit the nucleation of Aβ as well as the polymerization in pre-seeded fibril extension assays. In addition, it was shown that cholyl-LVFFA-OH delays the onset of polymerization and the formation of neurotoxic amyloid species for both peptides Aβ(1-40) and A β(1-42), protecting neuronal cell lines against Aβ toxicity [83]. Unfortunately, the use of cholyl-LVFFA-OH as a therapeutic agent is restricted by its large propensity to be cleared up almost completely after the hepatic first pass [83].…”
Section: Inhibiting Aβ Aggregation By Small Rationallydesigned Peptidesmentioning
confidence: 98%
“…The five residue sequence, LPFFD, has attracted attention as a β-sheet breaking peptide. The sequence closely resembles the Aβ peptide residues L 17 VFFA 21 , and has been shown to prevent polymerisation of Aβ in vitro [113]. It has also been proposed that AD may be treated by intervention/prevention of fibrillogenesis, and characterisation of the kinetic parameters of fibril formation with the intention of identifying a vulnerable structural transition has commenced [70].…”
Section: Future Targetsmentioning
confidence: 98%
“…The anionic disrupting compound KLVFFEEEE had similar effects, whereas the neutral compound KLVFFSSSS was ineffective, suggesting that the charged nature of the disrupting element is critical [55]. A different approach to design aggregation inhibitors was to add a bulky group to the recognition sequence, creating an inhibitor through steric hindrance [56,57]. The incorporation of N-methyl amino acids into peptides as disrupting elements has also been used by several investigators [58,59].…”
Section: Peptide Inhibitors Of Protein Misfoldingmentioning
confidence: 99%